Comparison of prescribing and dispensing processes between veterinarians and pharmacists in New Zealand: Are there opportunities for cooperation? - McDowell A; Assink L; Musgrave R; Soper H; Chantal C; Norris P (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
Prescribing and dispensing of medicines are fundamental processes in providing healthcare for both human and animal patients. There has been recent discussion in the literature to advocate for increased co-operation between pharmacists and veterinarians, however there is little data available about veterinary prescribing and dispensing processes.Objective: The aims of this study were to gain information on veterinary prescribing and dispensing processes in companion animals in the Dunedin region of New Zealand.Methods: Open interviews were conducted with a selection of five veterinarians at practices in Dunedin. All interviews were transcribed verbatim.Results: In New Zealand almost all dispensing of medicines for animals is carried out by veterinarians or their staff. There is a lack of standard treatment guidelines and a lack of regulation around the treatment period for which medicines can be dispensed at one time (i.e. period of supply). Medicines for animals are sometimes dispensed by community pharmacies, where clients are experiencing financial difficulties or when particular medicines are not held by veterinary practices. Record keeping requirements and practices for veterinarians are similar to those for community pharmacies.Conclusions: Processes undertaken by veterinarians in terms of prescribing and dispensing were similar to pharmacists' practices for human patients and so there is opportunity for collaboration between the two professions. Pharmacists also have complementary knowledge about dosing and formulating medicines that can assist in delivering optimal healthcare to animal patients.